A Dramatic Odd–Even Oscillating Behavior for the Current Rectification and Negative Differential Resistance in Carbon‐Chain‐Modified Donor–Acceptor Molecular Devices. (11th January 2013) - Zhang, Zhenhua; Guo, Chao; Kwong, Denise Jeng; Li, Jie; Deng, Xiaoqing; Fan, Zhiqiang
Abstract The donor–acceptor molecule is the only molecule that features a real intrinsic rectification. However, all investigations in the last decades showed that rectification behaviors of such molecules are not promising since their rectification ratio is only on the order of 10. Use of carbon chains Cn to serve as spacers is reported, along with attempts to modulate electrical behavior of the donor–acceptor molecule. Calculations using the first‐principles method show that electrical behavior is indeed altered substantively, and a particular regularity can be clearly observed, i.e., a dramatic odd–even oscillation for electronic behavior with increasing carbon‐chain length n. For models with even‐n carbon chains, the rectification ratio is small (30), and no negative differential resistance (NDR) behavior is detected, but the rectifying performance of models with odd‐n carbon chains is tremendously improved and rectification ratios on the order of 50 to 400 can be achieved, alongside a large NDR. This study thus suggests that using a suitable spacer might be an effective way to significantly boost electrical characteristics, including rectifying performance, of the donor–acceptor molecule.